Oxidation behaviour of zirconium hydride and its influence on the thermal desorption kinetics. (15th April 2018) - Ma, Mingwang; Wang, Lei; Wang, Yuan; Xiang, Wei; Tang, Binghua; Lyu, Ping; Tan, Xiaohua
Highlights: Oxidation of ZrH2 is limited by oxygen grain boundary diffusion. The oxide formed on ZrH2 represents a layered structure. The thicker the oxide layer, the greater the influence on H2 desorption kinetics. Shrinking core model was proposed combined with Zr-H phase diagram. Abstract: The oxidation kinetics of zirconium hydride powder in air was studied over the temperature range of 100–300 °C. The oxidation kinetic parameters were obtained and a controlling mechanism was proposed. The XPS depth profile analysis was consistent with a layered structure of the oxide film. The evolution of oxygen concentration profile allowed to estimate the diffusion coefficient of oxygen in zirconium oxide. Thermal desorption behaviours of pre-oxidized ZrH2 were studied using simultaneous thermogravimetry and thermal desorption spectroscopy (TG-TDS). The phase transformation sequence during dehydrogenation process of pre-oxidized ZrH2 was established and a corresponding shrinking core model was proposed.